Is hybridization driving the evolution of climatic niche in Alyssum montanum - Arrigo, Nils; de La Harpe, Marylaure; Litsios, Glenn; Zozomová-Lihová, Judita; Španiel, Stanislav; Marhold, Karol; Barker, Michael S; Alvarez, Nadir (American journal of botany, 2016)
PREMISE OF THE STUDY: After decades of interest, the contribution of hybridization to ecological diversification remains unclear. Hybridization is a potent source of novelty, but nascent hybrid lineages must overcome reproductive and ecological competition from their parental species. Here, we assess whether hybrid speciation is advantageous over alternative modes of speciation, by comparing the geographical and ecological ranges and climatic niche evolutionary rates of stabilized allopolyploid vs. autopolyploids in the Alyssum montanum species complex. METHODS: We combined an extensive review of studies addressing the systematics and genetic diversity of A. montanum s.l., with flow cytometry and cloning of nuclear markers, to establish the ploidy level and putative hybrid nature of 205 populations. The respective geographic distribution and climatic niche evolution dynamics of the allo- and autopolyploids were investigated using multivariate analyses and comparative phylogenetic approaches. KEY RESULTS: As expected by theory, allopolyploids occur mainly along contact zones and are generally spatially overlapping with their diploid counterparts. However, they demonstrate higher rates of niche evolution and expand into different climatic conditions than those of their diploid congeners. In contrast, autopolyploids show lower rates of niche evolution, occupy ecological niches similar to their ancestors and are restricted to less competitive and peripheral geographic areas. CONCLUSIONS: Hybridization thus seems advantageous by promoting ecological niche evolution and more readily allowing escape from competitive exclusion.
Keywords: zeměpis; Phylogeny; Hybridization, Genetic; minority cytotype disadvantage; Geography; autopolyploidy; ecological novelty; Biological Evolution; local adaptation; hybridizace genetická; Brassicaceae; genetická variace; Genetic Variation; Ploidies; ploidie; Diploidy; fylogeneze; biologická evoluce; Climate; allopolyploidy; diversification; transgressive segregation; podnebí; ekologie; competition; Ecology; diploidie